2015
DOI: 10.1039/c5cc00686d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 reduction by a mixed metal (Zr/Ti), mixed ligand metal–organic framework under visible light irradiation

Abstract: Postsynthetic exchange (PSE) of Ti(IV) into a Zr(IV)-based MOF enabled photocatalytic CO2 reduction to HCOOH under visible light irradiation with the aid of BNAH and TEOA. Use of a mixed-ligand strategy enhanced the photocatalytic activity of the MOF by introducing new energy levels in the band structure of the MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
229
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(236 citation statements)
references
References 38 publications
2
229
0
5
Order By: Relevance
“…Due to the formation of oxo-bridged bimetallic assemblies in an MOF material, the metal-to-metal charge transfer (MMCT) occurs, leading to the enhanced photocatalytic performance. [119] The turnover number of NH 2 -UiO-66(Zr/Ti) (4.66 ± 0.17) was higher than that of NH 2 -UiO-66(Zr) (1.52). [118] They found that the introduction of Ti ions into Zr 6 O 4 (OH) 4 SBUs not only enhanced the CO 2 adsorption capability ( Figure 8c 4 SBUs of NH 2 -UiO-66(Zr) via a PSE method and examined its performance for photocatalytic CO 2 reduction under visible-light irradiation in MeCN solvent with 1-benzyl-1,4-dihydronocotinamide (BNAH) as a sacrificial reductant and TEOA as a sacrificial agent.…”
Section: Othersmentioning
confidence: 86%
See 2 more Smart Citations
“…Due to the formation of oxo-bridged bimetallic assemblies in an MOF material, the metal-to-metal charge transfer (MMCT) occurs, leading to the enhanced photocatalytic performance. [119] The turnover number of NH 2 -UiO-66(Zr/Ti) (4.66 ± 0.17) was higher than that of NH 2 -UiO-66(Zr) (1.52). [118] They found that the introduction of Ti ions into Zr 6 O 4 (OH) 4 SBUs not only enhanced the CO 2 adsorption capability ( Figure 8c 4 SBUs of NH 2 -UiO-66(Zr) via a PSE method and examined its performance for photocatalytic CO 2 reduction under visible-light irradiation in MeCN solvent with 1-benzyl-1,4-dihydronocotinamide (BNAH) as a sacrificial reductant and TEOA as a sacrificial agent.…”
Section: Othersmentioning
confidence: 86%
“…[115] Under visible-light irradiation for 10 h, the amount of HCOO − produced by NH 2 -UiO-66(Zr) reached about 13.2 µmol. [119] The turnover number of (NH 2 ) 2 -UiO-66(Zr/Ti) (6.27 ± 0.23) was higher than that of parent NH 2 -UiO-66(Zr/Ti) (4.66 ± 0.17) (Figure 9b). Lee 83 (also called (NH 2 ) 2 -UiO-66(Zr/Ti)) photo catalysts by using a small amount of (NH 2 ) 2 -BDC as a coligand into NH 2 -UiO-66(Zr) or NH 2 -UiO-66(Zr/Ti) (Figure 9a), and confirmed that the increase of the amino group number made new energy levels in the band structure form and the light-absorption range become broadened, leading to improved photocatalytic activities.…”
Section: Amino Modificationmentioning
confidence: 94%
See 1 more Smart Citation
“…Lee et al employed postsynthetic exchange to introduce Ti into UiO-66(Zr) as well as a mixed-ligand strategy to achieve photocatalytic CO 2 reduction to formic acid with a TON ∼6.3. 36 Recently, Wang et al reported efficient proton and CO 2 reduction using Co-ZIF-9 (ZIF = zeolitic imidazolate framework) in conjunction with [Ru(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) as a photosensitizer and TEOA as a sacrificial reductant, reaching a TON for CO as high as 89.6 within 30 min. 37 However, the mechanism for this high activity was not discussed, and the selectivity for CO 2 reduction against proton reduction was low (CO:H 2 ratio = ∼1.4:1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…OH)4 in Ti-doped NH 2 -UiO-66(Zr). However,owing to the overlap of the electronic states of Zr and Ti atoms in Ti-doped NH 2 -UiO-66(Zr), Ti 3+ can further transfer electrons to Zr 4+ to form the photocatalytically active Zr 3+ .T hus,i ti sp roposed that the substituted Ti moiety may act as an electron mediator in promoting the electron transfer from 2-atp to the Zr center (Scheme 10).Recently,aphotocatalyst obtained by post-synthetic exchange through mixed-ligand, mixed-metal of UiOreported to be an effective photocatalyst for CO 2 photoreduction under visible-light irradiation [99]. Thekey reason for substituting Ti IV ions in NH 2 -UiO-66 is to make the SBUs more capable of accepting electrons generated via light absorption by the organic linkers.O nt he other hand, introduction of asmall amount of dta as aco-ligand provides new energy levels in the band structure of the MOF and favors abroader wavelength range of light absorption for the mixedligand MOF (Scheme 11).…”
mentioning
confidence: 99%